Regulatory T cell subsets in peripheral blood of HIV-infected patients with discordant response to antiretroviral therapy - L. B. Korolevskaya; E. V. Saidakova; N. G. Shmagel; K. V. Shmagel (Медицинская иммунология, 2020)
The discordant immunologic response to antiretroviral therapy in HIV-infected patients is characterized by ineffective recovery of CD4+T cell counts. The role of regulatory T cells in discordant response to the treatment remains poorly understood both due to the lack of specific and reliable markers of regulatory T cells and their subset’s heterogeneity. In the present work, we studied two groups of HIV-infected patients receiving antiretroviral therapy for more than two years and thus having their viral load suppressed (less than 50 copies of HIV per ml of blood): those who responded (n = 22) and did not respond (n = 19) to the treatment with an increase in their CD4+T cell counts. The control group consisted of uninfected volunteers (n = 23). The CD4+T lymphocyte subset composition was examined by flow cytometry. It was shown that in HIV-infected patients with ineffective immune recovery compared with subjects having a standard response to antiretroviral therapy, the absolute counts of regulatory T cells, as well as CD4+T lymphocytes, was reduced in all maturational subsets: naive cells, central memory, effector memory, and terminally differentiated effectors. That differed immunological nonresponders from patients with a standard response to the treatment, which had a shortage only in naive and central memory regulatory T cell subsets. It is important to note that in HIV-infected patients with a discordant response to therapy, the proportion of effector memory regulatory T cells, that posses the most prominent suppressive capacity, was significantly increased compared with that in other CD4+T lymphocyte subsets. Apparently, despite of regulatory T cell deficiency, in HIV-infected patients with a discordant response to the treatment, the regulatory T cell pool size is big enough to control CD4+T lymphocyte activation. Nevertheless, the number of regulatory T cells may not be sufficient to suppress the over-activation of immunocompetent cells that are not in the CD4+T lymphocyte subset. This can partly explain the increased cell activation level in patients with a discordant response to therapy as compared with those who have a standard respond to the treatment.